2007
DOI: 10.1159/000111595
|View full text |Cite
|
Sign up to set email alerts
|

Nonhemorrhagic Primary Obstetric Shock

Abstract: Objective: Clinical evaluation of nonhemorrhagic primary obstetric shock (NHPOS). Methods: In a retrospective clinical study, data on 8 cases of NHPOS were analyzed. Data on patient age, parity, week of gestation, comorbidity, possible etiologic trigger, course of disease with clinical picture and laboratory findings of coagulopathy, and patient outcome including autopsy findings in two lethal outcomes were analyzed. Results: These 8 patients were treated in the intensive care unit. One patient died during del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
1
0
2
Order By: Relevance
“…Other studies have shown that cesarean delivery poseda higher risk of hysterectomy (OR = 1.30), obstetric shock (OR = 2.54), and anesthetic complications (OR = 2.18) [30]. Obstetric shock includes bleed-ing shock, pulmonary embolism, amniotic fluid embolism, and sepsis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that cesarean delivery poseda higher risk of hysterectomy (OR = 1.30), obstetric shock (OR = 2.54), and anesthetic complications (OR = 2.18) [30]. Obstetric shock includes bleed-ing shock, pulmonary embolism, amniotic fluid embolism, and sepsis [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Somit ist eine definitive Diagnose der Fruchtwasserembolie trotz Autopsie im Einzelfall schwierig, wenn nicht unmöglich. Für diese Fälle ist der nichthämorrhagische, primäre geburtshilfliche Schock ("nonhemorrhagic primary obstetric shock", NHPOS) wohl eine treffendere Bezeichnung [16].…”
Section: Pathophysiologie Und Klinikunclassified
“…임신중 패혈성쇼크는 드물지만 모성사망의 주요 원인이며 태아에게 치명적인 경과를 초래할 수 있다 [1,2]. 원인은 감염성유산이 대표적이나 신우신염 등 비산과적인 원인으로 발생할 수도 있으며 실제로 원인을 밝힐 수 없는 경우도 많다.…”
unclassified